Correlative effect of critical parameters for η recrystallization texture development in rolled Fe81Ga19 sheet: Modeling and experiment. (1st April 2019) - Fu, Q.; Sha, Y.H.; Zhang, F.; Esling, C.; Zuo, L.
Abstract: Strong η (<100>∥RD, rolling direction) recrystallization texture is successfully developed through thickness in Fe81 Ga19 sheets with fine-grained microstructure by primary recrystallization process. An excellent combination of magnetic and mechanical properties is achieved with magnetostriction coefficient of 150 ppm, yield strength of 608 MPa and elongation of 11.7%. Quantitative macro/micro-texture analysis indicates that the enhanced η texture derives from number and size advantages established by preferred nucleation and efficient growth. The highly attractive phenomenon is that deformed grains with α (<110>∥RD) texture can be extensively consumed by η recrystallized grains in addition to deformed grains with γ (<111>∥ND, normal direction) texture. A physical model is proposed that well describes the relationship between strong η texture development in competition with γ and α recrystallization textures, where several critical parameters characteristic of deformation texture and microstructure are included. The correlative effect of these parameters are figured out based on the modeling and experimental data. The present work can provide an effective method for recrystallization texture design and control in body-centered cubic alloy sheets. Graphical abstract: Image 1